Personal and social determinants of Fear of Missing Out (FoMO) among university students in UiTM Lendu / Muhammad Harith Hairul … [et al.] - Hairul, Muhammad Harith; Hasbullah, Nur Qistina; Jamaludin, Nurul Syamimi; Mohd Isa, Sofea Hana; Zamsari, Zalikha; Hassan, Mohd Sufiean; Sah Allam, Siti Nurshahidah (Faculty of Communication & Media Studies, 2025)
The purpose of this study is to investigate the social and personal factors that influence university students at UiTM Lendu’s fear of missing out (FoMO). The main goals are to find out the amount of FoMO that students encounter, investigate the connection between FoMO and social and personal factors, and determine how it affects students’ social and personal results. Using a quantitative methodology, 419 respondents were chosen by cluster sampling. Structured questionnaires were used to gather data, and SPSS version 20 was used for analysis. Variable levels were evaluated using descriptive statistics, and the associations and effects of social media use, social support, and social comparison on FoMO were investigated using multiple regression analysis and Pearson correlation. The findings showed that students’ levels of FoMO ranged from moderate to high, and there were noteworthy connections between FoMO and the determinants under investigation. By offering insightful information on the variables affecting FoMO, this study advances our knowledge of how it affects college students’ well-being.